2014
DOI: 10.4103/0972-5229.140154
|View full text |Cite
|
Sign up to set email alerts
|

Permissive hypercapnia: Is there any upper limit?

Abstract: A 19-year-old male presented with history of massive hemoptysis. The patient was kept on mechanical ventilation because of severe hypoxia. Lung protective ventilation with low tidal volume was given in view of very poor pulmonary compliance. During the course of treatment, the patient developed a very high CO2 level of 373 mmHg. The patient was successfully weaned off on the 9th day without any obvious adverse consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We read the article by Garg SK “Permissive hypercapnia: Is there any upper limit?”[ 1 ] with great interest. The author has rightly focused on a current protective lung ventilation strategy.…”
mentioning
confidence: 99%
“…We read the article by Garg SK “Permissive hypercapnia: Is there any upper limit?”[ 1 ] with great interest. The author has rightly focused on a current protective lung ventilation strategy.…”
mentioning
confidence: 99%
“…Garg et al considered that when oxygenation and circumfusion are sufficient, permissible hypercapnia (PHV) allows a maximum PaCO 2 of 67 mmHg and a minimum pH of 7.2 in arterial blood gas. 9) According to previous research, carbon dioxide artificial pneumothorax under low pressure (<8 mmHg) has no significant effect on respiration and circulation. 10) In our study, after 8 mmHg CO 2 insufflation, arterial blood gas analysis, and ventilator parameters indicated a decrease in pH and an increase in PetCO 2 and PaCO 2 , suggesting acidosis and hypercapnia within acceptable levels.…”
Section: Discussionmentioning
confidence: 96%
“…In current practice, mean maximum PaCO 2 and pH associated with permissive hypercapnia are around 67 mmHg and 7.2, respectively, ( 24 ). It was reported that hypercapnia can be well tolerated as long as tissue perfusion and oxygenation are preserved and there are no contraindications ( 25 ). But hypercapnia may cause cardiovascular and cerebrovascular problems and acid-base imbalance.…”
Section: Discussionmentioning
confidence: 99%